DAMPAK SANISTASI LINGKUNGAN TERHADAP KESEHATAN MASYARAKAT DI WILAYAH PESISIR KECAMATAN MEDAN BELAWAN - Susilawati Susilawati; Salsa Nabila Ananda (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
This study discusses the importance of clean water and proper sanitation in maintaining public health. The research aims to identify issues related to water sources and sanitation and their impact on skin health. Data collection methods included field observations and interviews with selected respondents. The findings reveal that a significant portion of the community in this area lacks access to adequate fecal disposal facilities. Toilets and sanitation facilities are often built along riverbanks, directly flowing into the sea. Moreover, the use of contaminated water sources, such as untreated river water, increases the risk of skin diseases. In terms of education, the majority of the community has primary-level education, with the primary occupation being fishing. In conclusion, poor sanitation and limited access to clean water significantly affect community health. Skin disorders and other environment-related illnesses are considered common. Therefore, the author recommends several steps to improve access to clean water and proper sanitation. These steps include enhancing clean water infrastructure, raising public awareness about personal hygiene, conducting regular water quality monitoring, constructing hygienic sanitation facilities, and fostering collaboration among stakeholders. This study is expected to provide a better understanding of the issues surrounding clean water and sanitation in the context of public health. The research findings can serve as a basis for planning and implementing programs aimed at improving access to clean water and proper sanitation, thus enabling communities to live in a healthy environment and prevent diseases